Durability performance of green concrete composites containing waste carpet fibers and palm oil fuel ash - Mohammadhosseini, Hossein; Mohamad Yatim, Jamaludin; Mohd Sam, Abdul Rahman; Abdul Awal, A.S.M. (Elsevier, 2017)
Cleaner production is a pressing concern of the 21st century. Waste materials resulting from different industrial processes requires proper management to ensure a cleaner environment. The use of recycled materials in new green concrete production is very attractive due to the low-cost related to the waste materials in addition to saving required space for landfill purposes and the development as well as improvement in the concrete properties. This paper focuses on the durability properties of green concrete composite, which comprised of waste polypropylene (PP) carpet fiber and palm oil fuel ash (POFA). Properties studied include slump and VeBe time of fresh concrete as well as water absorption, sorptivity, chloride penetration, carbonation, and drying shrinkage of hardened concrete. Carpet fiber of 20 mm in length and six volume fractions of 0e1.25% were used with ordinary Portland cement (OPC). Another six concrete mixes were cast whereby OPC was replaced by 20% POFA. It was observed that the combination of PP carpet fiber and POFA decreased the slump values and increased the VeBe time of the fresh concrete mixes. In addition, water absorption, sorptivity, chloride penetration, and carbonation depth of the concrete composite for both OPC and POFA content mixtures were reduced with the addition of carpet fiber, with volume fractions of up to 0.75%. The positive interaction between carpet fibers and POFA subsequently led to the lower drying shrinkage of the concrete composite. The influences of POFA on the durability performance of concrete was observed to be more significant at longer curing periods. The findings of the study demonstrated that there is a promising future for the use of waste carpet fibers as a fibrous material in the production of a green and durable concrete. Green concrete also minimizes solid wastes, improves air quality, and leads to sustainable cement and concrete industry.